Cooperation between the occupational health insurance and physicians practicing occupational dermatology: optimization potential in quality assurance - Elsner, Peter; Aberer, Werner; Bauer, Andrea; Diepgen, Thomas Ludwig; Drexler, Hans; Fartasch, Manige; John, Swen Malte; Schuhmacher-Stock, Uta; Wehrmann, Wolfgang; Weisshaar, Elke (Journal der Deutschen Dermatologischen Gesellschaft, 2014)
Quality assurance is a task of the medical profession, but it is also a duty of the occupational health insurance (OHI). Data on the interaction quality between physicians practicing occupational dermatology and the OHI are limited.An online survey was performed in 854 German members of the Working Group on Occupational and Environmental Dermatology in October 2013. Items included demographic data, a judgment on the cooperation between the dermatologists and OHI companies, an economic grading of the current compensation scheme, and prioritization of optimization tasks.182 members (21.3 % of the invited population) participated in the survey. The cooperation with the OHI companies was judged as "very good" by 10.8 %, as "good" by 56.7  %, as "satisfactory" by 24.2 %, as "sufficient" by 7.0 % and as "inadequate" by 1.3 %. 93.4 % of the interviewed mentioned problems and improvement potentials in the cooperation of their practice or clinic with OHI companies. Main points of criticisms were reimbursement (44.7 %), followed by impairments of the treatment options (36.5 %) and the delay or scope of the treatment in the dermatologist's procedure (29.4 %).While most physicians practicing occupational dermatology give a positive judgment of their cooperation with OHI companies, quality optimization potentials exist regarding the reimbursement of dermatological services, especially regarding time-intensive counselling in the prevention of occupational skin diseases, in the enablement of diagnostic and therapeutic procedures according to current guidelines and in a timely preventive intervention to use the therapeutic window before chronification of skin diseases may occur.
EVALuna2:9711